The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts. (28th June 2016) - Stephens, Patrick R.; Altizer, Sonia; Smith, Katherine F.; Alonso Aguirre, A.; Brown, James H.; Budischak, Sarah A.; Byers, James E.; Dallas, Tad A.; Jonathan Davies, T.; Drake, John M.; Ezenwa, Vanessa O.; Farrell, Maxwell J.; et al.
Abstract: Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.